Comparative analysis of hemodynamic parameters and heart rate variability in football and hockey players at the stage of sports improvement - Lavrichenko, V.; Lindt, T.; Kalinina, I.; Zolotarev, A. (BIO Web of Conferences, 2020)
The article presents a multi-year multicenter research material concerning the study of adaptive aspects of hemodynamic and vegetative homeostasis of athletes engaged in football and hockey at the stage of sports improvement. The following was revealed: both groups of athletes were characterized by the formation of a cardiovascular functional system with a state of minimal tension of regulatory mechanisms to maintain hemodynamic homeostasis. The total sum of ICVR indicators in the group of football players was -1 point, which, according to the classification, can be assessed as a state of some functional tension, manifested by the mobilization of protective mechanisms. The hockey players were observed to have an optimal state of the regulation systems tension. It is characteristic of a satisfactory adaptation of the body to environmental conditions (1 point). The vascular type of self-regulation of blood circulation is more optimal in the formation of adaptation to dynamic loads of variable intensity.